An innovative universal and selective service prevention among Young People: The National Cuida-te+ Program (“Take Care+ Program”) - Margarida Gaspar de Matos; Tania Gaspar; Marta Raimundo; Cátia Branquinho; Gina Tomé; Marta Reis; Catarina Noronha; Fábio Botelho Guedes; Ana Cerqueira (Análisis y Modificación de Conducta, 2025)
The Cuida-te+ Program (Take Care+ Program) of the Portuguese Institute of Sports and Youth aims to promote youth health and healthy lifestyles. It targets young people aged 12 to 25. Through the work developed by 19 Psychologists in the Psychologists in the Junior Professional Year, centered in the 18 districts of the mainland Portugal, the aim is to analyze the interventions carried out in the following settings: Mobile Units, Youth Health in Portal and Youth Health (Counseling) Offices. Considering the objective, a quantitative and qualitative methodology was used. The Cuida-te+ Program is innovative in the European space and promising in its objectives, resources, and proximity option. It has the greatest relevance in supporting young people in health prevention and promoting healthy lifestyles. This work includes guidelines that aim to raise awareness among the general population to implement interventions more focused on the needs of young people.